Faith-based organisations (FBO): A review of literature on their nature and contrasting identities with NGO in community development intervention - Asma Lailee Mohd. Noor; Noor Hisham Md Nawi (2016)
Organizations with a faith basis play a dominant role within the development sector. In the latter half of the twenty-first century, many faith-based organizations (FBOs), motivated by their religious faith and beliefs, began to work beyond their own borders to improve the material well-being of the world’s poor. However, despite the significant presence of FBOs within the arena of aid and development, little agreement exists within the development literature as to the similarity or distinction between aid agencies that are faith based and secular. This study reviews the existing literature on the nature of the FBOs in order to analyse how FBOs are understood in relation to NGOs. It also suggests a number of different typologies that captures these diverse ranges of views of how FBOs are understood.